2011
DOI: 10.1080/09602011.2011.627263
|View full text |Cite
|
Sign up to set email alerts
|

Imagine that: Self-imagination improves prospective memory in memory-impaired individuals with neurological damage

Abstract: Recent research has demonstrated that “self-imagination” – a mnemonic strategy developed by Grilli and Glisky (2010) – enhances episodic memory in memory-impaired individuals with neurological damage more than traditional cognitive strategies, including semantic elaboration and visual imagery. The present study investigated the effect of self-imagination on prospective memory in individuals with neurologically-based memory deficits. In two separate sessions, 12 patients with memory impairment took part in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 32 publications
2
36
1
Order By: Relevance
“…However, visualization was beneficial for naturalistic PM performance specifically among seropositive individuals with low time-based PM and/or intact learning. The benefit of visualization on event-based PM observed among this subset of young HIV+ individuals is consistent with prior studies in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012), older adults (Altgassen et al, 2015), and clinical samples (Grilli & McFarland, 2011; Potvin et al, 2011). Additionally, these data provide further evidence that inclusion of implementation intentions is not required for visualization to bolster event-based PM (Meeks & Marsh, 2010; McFarland & Glisky, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, visualization was beneficial for naturalistic PM performance specifically among seropositive individuals with low time-based PM and/or intact learning. The benefit of visualization on event-based PM observed among this subset of young HIV+ individuals is consistent with prior studies in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012), older adults (Altgassen et al, 2015), and clinical samples (Grilli & McFarland, 2011; Potvin et al, 2011). Additionally, these data provide further evidence that inclusion of implementation intentions is not required for visualization to bolster event-based PM (Meeks & Marsh, 2010; McFarland & Glisky, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…This hypothesis was supported by Brewer and Marsh (2010), who demonstrated that deeper encoding of the cue-to-context link by way of visualization was associated with better accuracy on event-based PM tasks. Further support for the association between brief visualization exercises utilized during the encoding stage of laboratory PM tasks and enhanced event-based PM has been shown in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012; Altgassen et al, 2015), older adults (Altgassen et al, 2015) individuals with traumatic brain injury (Potvin et al, 2011), and a mixed clinical sample with memory impairments (Grilli & McFarland, 2011). Visualization has also been associated with improvements in time-based PM in young adults (Altgassen et al, 2015), older adults (Altgassen et al, 2015), adult social drinkers (Griffiths et al, 2012), and individuals with moderate-to-severe traumatic brain injury (Potvin et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The CRTF reviewed 7 Class I studies, 37-43 7 Class II studies [44][45][46][47][48][49][50] and 6 Class III studies [50][51][52][53][54][55][56] addressing remediation of memory. Many of these studies focused on specific types of memory impairments rather than global memory functioning.…”
Section: Rehabilitation Of Memory Deficitsmentioning
confidence: 99%
“…Generalization was demonstrated by participants making fewer PM failures in their daily lives. Two Class II studies 45,46 investigated self-imagination as a mnemonic strategy to enhance episodic memory, with respect to a PM task. Participants who were trained on a self-imagination technique demonstrated a 66% advantage in prospective remembering, compared with just using rote rehearsal.…”
Section: Rehabilitation Of Memory Deficitsmentioning
confidence: 99%